Ischemic Stroke, Inflammation, and Endotheliopathy in COVID-19 Patients. Issue 6 (10th May 2021) - McAlpine, Lindsay S.; Zubair, Adeel S.; Maran, Ilavarasy; Chojecka, Pola; Lleva, Paul; Jasne, Adam S.; Navaratnam, Dhasakumar; Matouk, Charles; Schindler, Joseph; Sheth, Kevin N.; Chun, Hyung; Lee, Alfred I.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Reports indicate an increased risk of ischemic stroke during coronavirus disease 2019 (COVID-19) infection. We aimed to identify patients with COVID-19 and ischemic stroke and explore markers of inflammation, hypercoagulability, and endotheliopathy, a structural and functional disturbance of the vascular endothelium due to a stressor. Methods: This was a retrospective, observational cohort study comparing acute ischemic stroke patients with and without COVID-19 across 3 hospitals. Timing of stroke onset during COVID-19 course and markers of inflammation, hypercoagulability, and endothelial activation were evaluated by COVID-19 status and stroke cause. Results: Twenty-one patients with ischemic stroke were diagnosed with COVID-19 during the study period. Patients with COVID-19 had a similar age and burden of vascular risk factors compared with the control cohort (n=168). We identified a temporal correlation between stroke onset and the peak of acute phase reactants, including CRP (C-reactive protein), ferritin, and d-dimer. In subsets of patients with labs available, embolic stroke of undetermined source was associated with elevated IL (interleukin)-6 (median, 171 [interquartile range, 13–375] versus 8 [4–11], P <0.01) and sIL (soluble IL)-2 receptor (1972 [1525–4720] versus 767 [563–1408.5], P =0.05) levels. Stroke patients with COVID-19 demonstrated elevated levels of endothelial activation markers compared with non-COVID-19 stroke controls (median von Willebrand activity 285.0% [interquartile range, 234%–382%] versus 150% [128%–183%], P =0.034; von Willebrand antigen 330.0% [265%–650%] versus 152% [130%–277%], P =0.007, and factor VIII 301% [289%–402%] versus 49% [26%–94%], P <0.001). Conclusions: Ischemic stroke in patients with COVID-19 is associated with endotheliopathy and a systemic inflammatory response in patients with vascular risk factors. Further research evaluating endothelial and inflammatory markers in the setting of ischemic stroke and COVID-19 in larger, prospective cohorts is needed to validate the findings.